HUBUNGAN DUKUNGAN SOSIAL DAN TINGKAT KECEMASAN PADA KELOMPOK PEKERJA PNS YANG MENGHADAPI MASA PENSIUN DI POIGAR MINAHASA SELATAN - Ratu, Esterlani Waliani; Rompas, Sefti; Simak, Valen (Universitas Sam Ratulangi, 2021)
AbstractBackground of this research is Retirement is a time full of challenges because there are changessuch as from actively working to not working, from having a position to staying at home, fromgetting a high income to a lower income. Civil servants experience anxiety when facingretirement. This happens because there is no social support. Aim of this study was to determinethe relationship between social support and anxiety levels in the group of civil servants facingretirement in Poigar Minahasa Selatan. The research method used descriptive research withsamples, in this study there were 50 respondents obtained through total sampling. And using aquestionnaire research instrument and tested using Chi-square. The results of this study showedthat high social support had low anxiety as many as 25 people (100.0%). And low social supporthas high anxiety as many as 25 people (100.0%). The results of the analysis obtained value =0.000 <0.05. High Social Support has Low Anxiety as many as 25 people (100.0%). And lowsocial support has high anxiety as many as 25 people (100.0%). The results of the analysis socialsupport and anxiety levels in the group of civil servants facing retirement in Poigar MinahasaSelatan obtained value = 0.000 <0.05. Conclusion High social support has low anxiety whilelow social support has high anxiety. And there is relationship between social support and anxietylevels in the group of civil servants facing retirement.Keywords: Work; Social Support; Anxiety; RetirementAbstrakLatar Belakang Pensiun merupakan masa yang penuh tantangan karena terjadi perubahanseperti dari aktif bekerja menjadi tidak bekerja, dari memiliki jabatan menjadi diam di rumah,dari mendapat penghasilan tinggi menjadi penghasilan yang lebih rendah. Pegawai negeri sipilmengalami kecemasan ketika menghadapi masa pensiun. Hal ini terjadi karena tidak adadukungan sosial. Tujuan penelitian ini adalah untuk mengetahui hubungan dukungan sosial dantingkat kecemasan pada kelompok pekerja PNS yang menghadapi masa pension di poigarminahasa selatan. Metode penelitian menggunakan penelitian deskriptif dengan Sampel, padapenelitian ini berjumlah 50 responden yang diperoleh melalui total sampling. Dan menggunakaninstrumen penelitian Kuesioner dan di uji menggunakan Chi-square. Hasil penelitian didapatkanDukungan Sosial yang tinggi memiliki Kecemasan Rendah sebanyak 25 orang (50,0%). DanDukungan sosial rendah memiliki Kecemasan yang tinggi sebanyak 25 orang (50,0%). Hasilanalisa dukungan sosial dan tingkat kecemasan pada kelompok pekerja PNS yang menghadapimasa pension di poigar minahasa selatan diperoleh Ï value = 0,000 < 0,05. KesimpulanDukungan Sosial yang tinggi memiliki Kecemasan Rendah sedangkan dukungan sosial rendahmemiliki kecemasan yang tinggi. Dan terdapat hubungan dukungan sosial dan tingkat kecemasanpada kelompok pekerja PNS yang menghadapi masa pensiun.Kata Kunci : Bekerja; Dukungan Sosial; Kecemasan; Pensiun